The Effect of Consumer Ethnocentrism on Purchasing Batik Products: Application of the Extended Theory of Planned Behaviour (TPB) and Price Sensitivity - Vigory Gloriman Manalu; Fauziyah Adzimatinur (Budapest International Research and Critics University, 2020)
The growing globalization of markets, the bilateral free trade agreements and the development of free trade zones have made the pattern of ethnocentrism of consumers a crucial concern for multinational corporations operating outside their domestic market. Although consumer ethnocentrism is a global phenomenon, there are differences, depending on the country studied, in the degree expressed by consumers. The purpose of this study was to explore the effect of consumer ethnocentrism on purchase intention of domestic batik products compared to imported Batik through TPB and to determine the variables of price sensitivity and attitude as mediation. Data collection was carried out through printed questionnaires using a purposive sampling approach. The questionnaire had collected 200 respondents. Further testing used the equation modelling (SEM) structure. The empirical results of SEM show that all the proposed hypotheses are accepted.